2017
DOI: 10.1111/mmi.13874
|View full text |Cite
|
Sign up to set email alerts
|

An acetylatable lysine controls CRP function in E. coli

Abstract: Transcriptional regulation is the key to ensuring that proteins are expressed at the proper time and the proper amount. In Escherichia coli, the transcription factor cAMP receptor protein (CRP) is responsible for much of this regulation. Questions remain, however, regarding the regulation of CRP activity itself. Here, we demonstrate that a lysine (K100) on the surface of CRP has a dual function: to promote CRP activity at Class II promoters, and to ensure proper CRP steady state levels. Both functions require … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 77 publications
1
23
2
Order By: Relevance
“…While the precise delay identified by our analysis was not consistent with that observed in experiments, studies confirmed that a delay existed between crp induction and the induction of several target genes (36). This delay can possibly be attributed to posttranslational modification of crp (37). Of 32 edges in the gold standard, SWING identified 27 true-positive (TP) edges and 5 false-positive (FP) edges (85% TP), while the ensemble model predicted 24 TP edges and 8 FP edges (75% TP).…”
Section: Swing Accurately Infers Regulondb Modules With Time-delayedcontrasting
confidence: 78%
“…While the precise delay identified by our analysis was not consistent with that observed in experiments, studies confirmed that a delay existed between crp induction and the induction of several target genes (36). This delay can possibly be attributed to posttranslational modification of crp (37). Of 32 edges in the gold standard, SWING identified 27 true-positive (TP) edges and 5 false-positive (FP) edges (85% TP), while the ensemble model predicted 24 TP edges and 8 FP edges (75% TP).…”
Section: Swing Accurately Infers Regulondb Modules With Time-delayedcontrasting
confidence: 78%
“…In this case, we observed that the transcriptional response of the strain ΔN differs markedly from the one observed in the wild type strain when tested along 8,862 genes ( R 2 = 0.4406, see Figure S1 ). In any case, beyond of the critical experimental details mentioned, the theory presented by Davis et al ( 2018 ) does not seem to assign any role to the Δ crp (R-type) mutant (i.e., the CRP deacetylated ) for which we have also observed specific, significant effects. Neither does the proposal account for the group of genes that we have herein detected as being equally influenced by both CRP acetylated and CRP deacetylated .…”
Section: Discussioncontrasting
confidence: 63%
“…Recently, it has been suggested that the Δ crp (Q-type) mutant (i.e., the CRP acetylated ) exerts an inhibitory effect on the CRP-driven genes containing the type II promoters, while possibly also simultaneously exerting a positive effect on the CRP-driven genes containing the type I promoters (Davis et al, 2018 ). However, the hypothesis of the opposed effect of CRP acetylated depending on the type of promoter still remains to be experimentally verified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once formed, Ac-P could acetylate a variety of different proteins during diauxic shifts ( Figure 6 ) that are related to the glucose metabolism ( Kuhn et al, 2014 ; Venkat et al, 2017 ). Another possibility arises from a recent study ( Davis et al, 2018 ) that show that acetylation of CRP can also control its activity. Although ppGpp is not controlling the diauxic shift through changes in CRP expression, it might control it by changing its activity through acetylation.…”
Section: Discussionmentioning
confidence: 99%